Upaya Orang Tua Untuk Membentuk Kebiasaan Positif dalam Penggunaan Internet Di Kalangan Generasi Z di Desa Balimbingan Kecamatan Tanah Jawa - Wahyuni, Rifa; Yusnadi (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The rapid expansion of the internet in rural areas presents both opportunities and challenges for Generation Z, necessitating parental involvement in fostering positive internet usage habits. This study aims to describe the level of parental effort in shaping positive internet usage habits among Generation Z in Balimbingan Village, Tanah Jawa District. A descriptive quantitative approach was employed, involving a population of 778 families and a sample of 89 parents selected via simple random sampling. Data were collected using a Likert-scale questionnaire comprising 27 valid items and analyzed using descriptive statistics. The results indicate that the level of parental effort falls into the